Gender, color/race and literacy rates in Santa Catarina and Alagoas: an experiment based on micro data from the 2000 census - Alceu Ravanello Ferraro; Jasom de Oliveira (Universidade Federal de Santa Catarina, 2010)
Using micro-data from the 2000 Census, the study proposes to confront the relations of gender and color and race with literacy levels in Santa Catarina (SC) and Alagoas (AL) states, which are representative of extreme situations in the country in terms of school education. The study only considered young people from 18 - 24, who, because of their age, could or should have fi nished elementary school, which corresponds to level 4 literacy. These young people from 18-24 were classifi ed in different literacy levels based on the number of years of study they had passed. The study had three main fi ndings: first, while higher levels of literacy predominate in Santa Catarina, in Alagoas the lowest levels predominate; second, in both states, women have better literacy levels than men; third Santa Catarina as well as Alagoas has the following decreasing order in the literacy levels: 1st - white women, 2nd - white men, 3rd - black women, 4th - black men, that is, superiority of both women in relation to men and of whites in relation to blacks. In summary, while historic regional inequalities are maintained and those of color and race, young women from 18 - 24 have better literacy levels than men of the same age. The main challenge presented by these results is in the investigation and political and pedagogical confrontation of the causes, which, while they lead to an inversion in the relationship of inequality concerning gender, maintain and reproduce the educational inequalities related with the variables of region, color and race.